Penyuluhan interaktif tentang kesiapan mental ibu muda dalam mengelola tumbuh kembang anak - Dewi, Indah Maulina; Rum, Malihah Ramadhani; Indriyani, Hajir; Silahoy, Ice Meriah Hertanti; Daeli, Joverius; Erawati, Nieke; Krisna, Krisna; Auliah, Devi; Anisah, Dhea Muthia; Maura, Melisa Safa (Indonesian Public Health-Observer Information Forum (IPHORR) Kerja sama dengan: Unit Penelitian dan Pengabdian Kep Akademi Keperawatan Baitul Hikmah, 2025)
Background: The mental health of young mothers is a crucial aspect influencing family well-being and child development. However, mental health literacy among this group is still limited, necessitating educational efforts through appropriate counseling methods. Health promotion is the process of